1993
DOI: 10.1093/ageing/22.1.37
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Age with Gastric Emptying

Abstract: Gastric emptying is important as a rate-limiting step in the absorption of orally administered drugs. Paracetamol absorption kinetics were used to compare gastric emptying in 19 fit elderly and 19 fit young volunteers. The results showed no significant difference in any of the derived parameters (t1/2abs, tlag and tmax) between the two groups. These results suggest that ageing does not impair this rate-limiting step in drug absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…The effect of age per se on gastric emptying has received little attention, but appears to be stable in healthy humans [26]. The stability of this rate with age in healthy, non-diabetic animals seen in the present study is in agreement with the concept that gastric emptying is primarily controlled by calories [27].…”
Section: Figsupporting
confidence: 90%
“…The effect of age per se on gastric emptying has received little attention, but appears to be stable in healthy humans [26]. The stability of this rate with age in healthy, non-diabetic animals seen in the present study is in agreement with the concept that gastric emptying is primarily controlled by calories [27].…”
Section: Figsupporting
confidence: 90%
“…Although earlier studies reported significant apparently age-related effects including reduced gastric acid secretion [37,38] and gastric emptying [39], reduced splanchnic blood flow [40], and absorptive capacity of the small intestine [41], probably due to the effects of disease states, more recent reports have not confirmed these findings in healthy subjects [23,25,42,43].…”
Section: Drug Absorptionmentioning
confidence: 91%
“…This may be the direct consequence of changes in the enzyme secreting cells and organs or hormonal and neural regulatory alterations [22]. By contrast, gastric emptying in elderly subjects is similar to that of young subjects [23].…”
Section: Stomach and Duodenummentioning
confidence: 97%
See 1 more Smart Citation
“…The elderly tend to satiate earlier than young people after a meal; this early satiety is thought to be the consequence of signals emitted from the stomach. Most studies agree that a slower gastric emptying and a faster passage from the gastric fundus to the antrum occur with age (96). Food therefore remains in the antrum for a longer time, inducing a greater gastric distention.…”
Section: Anorexia In the Elderlymentioning
confidence: 96%